Quality assessment of matching single-cone obturation in canals Shaped with different NiTi systems : a micro-CT study = Evaluación de la calidad de la obturación de conductos radiculares con cono único : un estudio de micro-CT - Öztürk, Ayşenur 1991-; Haznedaroğlu, Faruk; Keleş, Ali; Kutlu Basmaci, Gülsüm (2024)
This study is aimed to evaluate the compatibility of single-cone filling technique in reciprocal and rotationally formed canals in using Micro-CT (Micro-computed tomography). The samples were split into two groups according to the kinematics system used. In both groups, one canal of the shaped roots was filled with the lateral compaction and the other one with a matched single-cone technique with a bioceramic root canal sealer, BioRoot RCS. The percentage of voids in the canal were evaluated by micro-CT radiograph before and after obturation. Regardless of the kinematics used, the single-cone technique left significantly fewer voids than the lateral compaction. In the kinematics comparison, the group shaped with the reciprocal system and filled with the single-cone system had the best results. The reciprocal nickel-titanium (NiTi) system with a matching single-cone gutta percha filling technique was found to be more effective in terms of reducing voids in root canal filling.
Este estudio evaluó la compatibilidad de la técnica de obturación de cono único mediante el uso de Micro-CT (microtomografía computarizada). Las muestras se dividieron en dos grupos según el sistema rotatorio utilizado. En ambos grupos, el conducto se obturó con compactación lateral y el otro con una técnica de cono único combinada con el cemento biocerámico BioRoot RCS. El porcentaje de espacios vacíos en el conducto se evaluó mediante micro-CT antes y después de la obturación. Independientemente de la cinemática utilizada, la técnica de cono único dejó significativamente menos espacios que la compactación lateral. El grupo conformado con el sistema recíproco y obturado con el sistema de cono único obtuvo los mejores resultados. El sistema recíproco con una técnica de obturación de gutapercha de cono único es más eficaz en términos de reducir los espacios vacíos en el conducto radicular.
En revista Odóvtos, vol. 26, no.3 (setiembre-diciembre 2024)
Descripción basada en el contenido visto el 07 de febrero, 2025
También disponible en formato HTML y EPUB